Phytochemical studies and bioactivity of selected species from the family melastomataceae / Norfaizah Mahmud - Mahmud, Norfaizah (2014)

(untitled)
The Melastomataceae is a large family of flowering plants consisting of trees, shrubs as well as epiphytes and are found throughout the tropics including Malaysia. However, only a handful of species have been studied for their phytochemical properties including the ones found in Malaysia. The present study was undertaken to evaluate the cytotoxic activities of the crude methanol (CME), ethyl acetate (CEE) and hexane extracts (CHE) of four selected wild species namely Melastoma muticum, Melastoma sanguineum, Memecylon caeruleum and Phyllagathis rotundifolia. Extracts of these species were prepared from the leaves and cytotoxic activities were screened by an in vitro assay system of growth inhibition against human breast MCF-7 cancer cell lines and human ovarian SKOV-3 cancer cell lines. CEE of P. rotundifolia exhibited the most potent cytotoxicity on MCF-7 cell lines (IC50 = 0.92 ± 0.01 μg/ml, SI = 8.22), while CEE of M. caeruleum possessed high cytotoxicity on SKOV-3 cell lines (IC50 = 16.04 ± 1.68 μg/ml, SI = 3.26). Qualitative phytochemical studies of the CME of the selected species revealed the presence of phenols, flavonoids, and tannins. Identification of the major compounds in CEE of P. rotundifolia and M. caeruleum were done by using LC-MS/MS system and phenolic groups were detected as the major compounds in both extracts. Total Phenolic Content (TPC) assay was done to measure the phenolic contents of each extract and CME of M. sanguineum exhibited the highest phenolic contents (718.18 ± 8.91 mg GAE/100 g). Antioxidant properties were studied by Ferric Reducing Antioxidant Power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays and CME of M. sanguineum was found to show the highest reducing activities (68.89 ± 0.50 μM/100 g) while CME of M. muticum exhibited the high free radical scavenging activities (IC50 = 77.1 ± 2.8 μg/ml).